Evaluating The Financial Performance Of Syrian Private Conventional Banks During The Syrian Crisis (Analytical Study On Two Conventional Private Banks Using CAMEL Model) - Khader, Qais; Harfoush, Yazan (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research aimed to shed light on the work of the traditional private banking sector during the period of the Syrian crisis, and measure the performance of this sector, and to assess the financial performance of traditional private banks during the period between 2011 and 2017, the researcher relied on the deductive and inductive approaches through the collection of data from different sources and access On the previous studies, in order to form the theoretical framework of the research and descriptive analytical method, by studying the financial performance indicators of a sample of conventional banks, and used for this disclosures and financial statements of banks, then the researcher collected data, and then analyzed by CAMEL model. The researcher reached the most important results as follows: The private banking sector witnessed a decline in net profits in most of the crisis years, in addition to some banks saw losses in profits during the period of the Syrian crisis. Bank Audi achieved a strong rating according to the capital adequacy index, a satisfactory rating according to the asset quality adequacy index, a satisfactory rating according to the management quality index, a marginal rating according to profitability index, and a middle rating according to the liquidity management index. A satisfactory rating according to the asset quality adequacy index, a middle rating according to the management quality index, a profitability index and a satisfactory liquidity rating. هدف البحث إلى إلقاء الضوء على عمل القطاع المصرفي الخاص التقليدي خلال فترة الأزمة السورية, وقياس أداء هذه القطاع, وتقييم الأداء المالي لمصرفين خاصين تقليديين خلال الفترة الواقعة بين عامي 2011 و2017, وأعتمد الباحث على المنهجين الاستنباطي والاستقرائي وذلك من خلال تجميع البيانات من المصادر المختلفة والاطلاع على الدراسات السابقة، بهدف تكوين الإطار النظري للبحث وعلى المنهج الوصفي التحليلي، من خلال دراسة مؤشرات الأداء المالي لعينة من المصارف التقليدية, واستخدم من أجل ذلك الإفصاحات والقوائم المالية للمصارف, ثم قام الباحث بجمع البيانات, ومن ثم تحليلها وفق نموذج CAMEL. وتوصل الباحث على أهم النتائج التالية: شهد القطاع المصرفي الخاص انخفاضاً في صافي الأرباح في معظم سنوات الأزمة, بالإضافة إلى أن بعض المصارف شهدت خسائر في أرباحها خلال فترة الأزمة السورية. حقق مصرف عودة تصنيفاً قوياً وفق مؤشر كفاية رأس المال, وتصنيفاً مرضياً وفق مؤشر كفاية جودة الأصول, وتصنيفاً مرضياً وفق مؤشر جودة الإدارة, وتصنيفاً حدياً وفق مؤشر الربحية, و تصنيفهما وسطاً وفق مؤشر إدارة السيولة, حقق مصرف سورية والمهجر تصنيفاً قوياً وفق مؤشر كفاية رأس المال وتصنيفاً مرضياً وفق مؤشر كفاية جودة الأصول, وتصنيفاً وسطاً وفق مؤشر جودة الإدارة, وتصنيفاً وفق مؤشر الربحية, وتصنيفاً مرضي وفق مؤشر إدارة السيولة.